Mengarahkan Transisi Hijau: Interaksi Tata Kelola Pemerintahan, Efektivitas Keuangan Hijau, dan Transformasi Struktural di Negara Berkembang - Fauzan Sinatra; R Fawwaz Zaidan Pradipa; I Putu Wedana; Muhammad Fadhil Kasmuddin; Arina Romaina; Ardieansyah Ardieansyah; Luthfi Azhari (Lembaga Pengembangan Kinerja Dosen, 2026)
This article aims to critically analyze the interaction between green finance (GF) and green government (GG) in the context of development economics. The main focus is to evaluate how the quality of institutional governance moderates the effectiveness of green finance flows in achieving a sustainable transition. Based on this analysis, this research proposes a new conceptual model. This study uses a Systematic Literature Review (SLR) methodology on Scopus and Sinta-indexed scientific articles, as well as reputable institutional reports (OECD, World Bank, IFC) within the 2020-2025 timeframe. This approach is combined with theoretical model development to synthesize findings. The review identifies a